PROSES ANTRIAN DENGAN KEDATANGAN BERDISTRIBUSI POISSON DAN POLA PELAYANAN BERDISTRIBUSI GENERAL - Sugito, Sugito; Hoyyi, Abdul (MEDIA STATISTIKA, 2013)
In the queuing process,   the distribution testing is performed to obtain the distribution of arrival and service distributions. Customer arrival distribution is obtained based on the number of arrivals or inter-arrival time. Service distribution is obtained based on the number of arrivals or inter-arrival time. In this paper we will discuss the process in queuing with the arrival of the Poisson distribution and the general pattern of service distribution   Keywords : Queuing,  Arrival Distribution, Service Distribution